2020
DOI: 10.1186/s43066-020-00062-8
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 polymorphism as a diagnostic tumor marker for hepatocellular carcinoma in patients with hepatitis C-related cirrhosis

Abstract: Background Egypt has the highest hepatitis C virus prevalence worldwide where about 24% of the people are estimated to carry HCV and more than 50% of blood donors have anti-HCV in some towns. The burden of hepatocellular carcinoma has been increasing in Egypt with a doubling in the incidence rate in the past 10 years. Thus, the aim of the present study was to analyze the interleukin-18 single nucleotide polymorphisms (SNPs) as a diagnostic tumor marker for hepatocellular carcinoma in patients with hepatitis C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Therefore, the expression of rhIL-18 and an antiapoptotic mechanism involving NF-κB activation in HCC cells may be related to poor prognosis in HCC patients [ 53 ]. Corroborating with these findings, a 2020 study indicated that IL-18 single nucleotide gene polymorphism could be a marker for HCC in patients with HCV-related cirrhosis [ 54 ], and IL-18 gene polymorphisms could be used as a potential non-invasive diagnostic tool for HCC patients at early stages [ 55 ], which is supported by recent findings that IL-18 high levels are found in HCC patients with poor prognosis [ 56 ].…”
Section: Il-1β and Il-18 In Liver Cancer Progressionmentioning
confidence: 87%
“…Therefore, the expression of rhIL-18 and an antiapoptotic mechanism involving NF-κB activation in HCC cells may be related to poor prognosis in HCC patients [ 53 ]. Corroborating with these findings, a 2020 study indicated that IL-18 single nucleotide gene polymorphism could be a marker for HCC in patients with HCV-related cirrhosis [ 54 ], and IL-18 gene polymorphisms could be used as a potential non-invasive diagnostic tool for HCC patients at early stages [ 55 ], which is supported by recent findings that IL-18 high levels are found in HCC patients with poor prognosis [ 56 ].…”
Section: Il-1β and Il-18 In Liver Cancer Progressionmentioning
confidence: 87%
“…Hepatic encephalopathy, a result of liver cirrhosis, was also positively correlated with IL-18 (21) . Studying IL-18 single nucleotide gene polymorphism may be a significant diagnostic for predicting cirrhosis progression in CHC patients, as the probability of developing HCC is 1.17-fold greater in those with the GC or CC genotypes compared to those with the GG genotype (22) . Vascular endothelial growth factor, which is involved in sinusoidal remodeling and the formation of portal-systemic collaterals in PH, is activated by IL-18, which plays a crucial role in the development of PH and esophageal varieces.…”
Section: Interleukin 18 In Liver Disease and Cirrhosismentioning
confidence: 99%